Permanent muscular sodium overload and persistent muscle edema in Duchenne muscular dystrophy: a possible contributor of progressive muscle degeneration - Weber, Marc-André; Wolf, Maya Barbara; Kauczor, Hans-Ulrich (Journal of neurology, 2012)
To assess the presence and persistence of muscular edema and increased myoplasmic sodium (Na+) concentration in Duchenne muscular dystrophy (DMD). We examined eight DMD patients (mean age 9.5 ± 5.4 years) and eight volunteers (mean age 9.5 ± 3.2 years) with 3-tesla proton (1H) and 23Na density-adapted 3D-radial MR sequences. Seven DMD patients were re-examined about 7 months later without change of therapy. The eighth DMD patient was re-examined after 5 and 11 months under medication with eplerenone. We quantified muscle edema on STIR images with background noise as reference and fatty degeneration on T1-weighted images using subcutaneous fat as reference. Na+ was quantified by a muscular tissue Na+ concentration (TSC) sequence employing a reference containing 51.3 mM Na+ with 5 % agarose. With an inversion-recovery (IR) sequence, we determined mainly the myoplasmic Na+. The normalized muscular 23Na IR signal intensity was higher in DMD than in volunteers (n = 8, 0.75 ± 0.07 vs. 0.50 ± 0.05, p < 0.001) and persisted at second measurement (n = 7, 1st 0.75 ± 0.07, 2nd 0.73 ± 0.06, p = 0.50). When compared to volunteers (25.6 ± 2.0 mmol/l), TSC was markedly increased in DMD (38.0 ± 5.9 mmol/l, p < 0.001) and remained constant (n = 7, 1st 37.9 ± 6.4 mmol/l, 2nd 37.0 ± 4.0 mmol/l, p = 0.49). Muscular edema (15.6 ± 3.5 vs. 6.9 ± 0.7, p < 0.001) and fat content (0.48 ± 0.08 vs. 0.38 ± 0.01, p = 0.003) were elevated in DMD when compared to volunteers. This could also be confirmed during follow-up (n = 7, p = 0.91, p = 0.12). Eplerenone slightly improved muscle strength and reduced muscular sodium and edema. The permanent muscular Na+ overload in all DMD patients is likely osmotically relevant and responsible for the persisting, mainly intracellular muscle edema that may contribute to the progressive muscle degeneration.
Gesehen am 28.03.2019